Unlocking Mathematical Thinking: Effective Learning Strategies for Primary Students in Nepal - Dhungana, Hem Lal; Khadka, Jaya Bahadur (Academic Journal of Mathematics Education, 2025)
This study investigates the learning strategies employed by students in mathematics at the basic level in Birendranagar, Surkhet. Grounded in Vygotsky’s sociocultural theory and critical pedagogy, the research adopts a descriptive statistic with quantitative data. A total of sixty students were randomly selected from three public and three private schools. Data were collected using a five-point Likert scale questionnaire and semi-structured interviews to identify cognitive, metacognitive, and social/affective strategies. Findings revealed that students predominantly relied on cognitive strategies such as memorization and repetition, while their use of metacognitive and social/affective strategies remained limited. Comparative analysis indicated little difference between students of public and private schools, though overall practices suggested a need for more balanced and reflective strategies to enhance learning outcomes. The study concludes that effective strategy use is essential for improving students’ mathematical understanding and achievement, and it recommends integrating contextualized, student-centered pedagogical practices to foster deeper and more sustainable learning.